CROSS-BORDER PUBLIC PROCUREMENT : A SYSTEMATIC LITERATURE REVIEW ON REGIONAL INTEGRATION, GOVERNANCE AND DIGITAL TRANSFORMATION - Elsa Sari Yuliana; Maria Christiana Iman Kalis; M. Irfani Hendri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study examines the development of research on cross-border public procurement or border procurement through a Systematic Literature Review (SLR) combined with bibliometric analysis. The study aims to identify publication trends, dominant research themes, key variables, and future research opportunities related to border procurement. Data were collected from the Scopus database using the PRISMA framework, resulting in 39 selected articles published up to May 2026. Bibliometric analysis was conducted using VOSviewer software to map publication trends, country distribution, institutional contributions, author productivity, and keyword co-occurrence networks. The findings reveal that research on border procurement remains relatively limited and is predominantly concentrated in developed countries, particularly within the European context. The literature mainly focuses on themes such as regulation and governance, digital procurement and transparency, regional market integration, sustainability, healthcare procurement, and barriers to cross-border procurement implementation. Several dominant variables identified in the literature include digital procurement, transparency, regulation, market integration, administrative barriers, sustainability, and competitive procedures. The study also highlights significant research gaps related to border procurement in developing countries and border regions outside Europe, particularly in ASEAN contexts. The integration of SLR and bibliometric analysis contributes to a more comprehensive understanding of the intellectual structure and thematic evolution of border procurement research. Practically, the findings provide insights for policymakers and practitioners in improving procurement governance, regulatory harmonization, digital transformation, and cross-border cooperation. The study recommends future research to explore procurement governance, digital readiness, and institutional challenges in developing-country border regions.